Enhancing Students’ English Vocabulary Through Unplugged Activities for Young Learners - Novita Mu’alifah, Indah (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
The aim of this research is to measure the effect of unplugged activities for young learners. The subject of this research has 2nd grade at MI Matholi’ul Falah Payaman there are 20 students. This research has classified as a pre-experimental design study, it involved one group pre-test post-test. From the result of the pretest researcher can conclude if the study on teaching vocabulary is low. The result shows that the differences on teaching vocabulary between pre-test and post-test is significant. By comparing the magnitude of “t” obtained in observational calculation (to=8,90) and then it can be known that the to is greater than tt 2,09<8,90. Because the to is bigger than tt then the Ho filed has rejected and Ha is accepted. This suggests that there is an effect on the use of unplugged activities on teaching vocabulary for young learners of 2nd grade at MI Matholi’ul Falah Payaman. From the explanation above the unplugged activities is effective on teaching vocabulary because the students a more active opportunity to learn vocabulary. The limitation of this research is using unplugged activities that conducted at MI Matholi’ul Falah Payaman. Novelty this research and another research is this research focus on teaching vocabulary by using unplugged activities for young learners.